Peningkatan Prestasi Akademik MIPA Pada Siswa Melalui Bimbingan Belajar - Bella Sukma Tris Sukarnawati Adinda; Suaibatul Aslamiyah (UNIB Press, 2022)
Education in the post-pandemic began to return to find strategies in normal learning, especially in elementary schools that must be considered. One of the efforts through tutoring is expected to be able to improve the academic achievement of students at MI in Gresik. The technique of implementing this activity uses the method of interviewing and observing with related parties. Observation is carried out by digging for information and observing the condition of students in learning mathematics and natural sciences during a pandemic. From the results of interviews with several teachers and homeroom teachers, there are several categories of selected students. Each class is represented by 6 students of the Mathematics category and 6 students of the science category. There were a total of 36 students from grades 4,5 and 6. The increase in achievement by selected grade 4-6 students can be observed by the teacher through the results of student learning achievement every semester.